Deictic settings in Lisa Robertson's The Weather. Issue 7 (9th August 2019) - Williams, Cameron
ABSTRACT: In a reading of Lisa Robertson's book of poems The Weather (2004), this essay considers how poetry can produce new knowledge in addition to curating cultural artifacts. Robertson's research poetics uses sound to articulate new discursive and social spaces – 'settings' – beyond her archive of meteorology, radio broadcasts, and feminist history. The poem poses the imagined community formed among the listeners of the popular Shipping Forecast in the UK as a model against which to question the possibility of an imagined feminist community.